Desenvolvimento de método voltamétrico para determinação de piridoxina em fármacos - Cottica, Solange Maria (2007)
A CrHCF-modified vitreous carbon electrode was used to determine pyridoxine (vitamin B6) in three drugs by cyclic voltammetry. The influence of several parameters on the voltammetric electrode response was analyzed. The linear range found was from 1.33 X 10-6 mol L-1 to 1.32 X 10-5 mol L-1 of vitamin, with r = 0.9990 and relative standard deviation of 4.2%. The limits of detection and quantification were 3.46 X 10-7 mol L-1 and 1.05 X 10-6 mol L-1, respectively. The voltammetric method proposed for the determination of vitamin B6 presented good accuracy and the experimental results demonstrated that the CrHCF-modified vitreous carbon electrode has a large potential for the analysis of pyridoxine in real samples. Furthermore, it has the advantages of a fast response, a low detection limit, low cost, and simple development and application.